RESPON BERBAGAI GALUR LOKAL PADI GOGO (Oryza sativa. L) TERHADAP DOSIS HARA N, P DAN K DI ULTISOL Responses of Local Cultivars Upland Rice to N, P and K Dosage at Ultisol - Yulhasmir, Yulhasmir (Universitas Muhammadiyah Palembang, 2014)
esearch on Responses of Local Cultivars Upland Rice to N, P and K Dosage at Ultisols, Experiments have been carried out in Research station of BLPP Agribisnis Raksa Jiwa (OKU), from the month of April 2013 to August 2013. The design used was split-plot design. The main plot was a level combinationt of nutrients N, P and K (H) with four doses of the: H0 (Without fertilization N, P and K), H1 (100 kg Urea/ ha, 50 kg SP-36/ha and 50 kg KCl/ha), H2 (200 kg Urea/ha, 100 kg SP-36/ha and 100 kg KCl/haI, H3 (300 kg Urea/ha, 150 kg SP-36/ha and 150 kg KCl/ha). Sub-plot was cultivars of upland rice (G) consisting of nine strains of the: G1 (strains Patek), G2 (strains Henik Bujuk), G3 (strains Henik Ijuk), G4 (strains Henik Pisang), G5 (strains Dayang Rindu), G6 (strains Sirendah), G7 (strains Pandan), G8 (strains Semester), G9 (Situ Bagendit). The parameters observed were the number of tillers, number of productive tillers, plant height, dry weight, plant age, time out of panicles, grain number/panicle, percentage grain content, grain weight/clump, and grain weight of 1000 grains.The result showed that there is a very significantly interaction between the cultivars with dosage of N, P and K, and no significant for the number of tillers, number of productive tillers, number of grains/panicle and grain weight/clump. Each of the strains showed growth characteristics and the results vary with fertilizer N, P and K. Henik Ijuk, Dayang Rindu, Henik Pisang, Sirendah, Henik Bujuk, Semeter and Patek strains grain yield per clump weight the higher the dose the greater the nutrient N, P and K and Pandan strains will show the weight of grain per clump lower with increasing doses N, P and K. Henik Ijuk strains produce higher grain production than the other strains. Dose of fertilizer that can be used for local upland rice cultivation is recommended to use a